Quantum Field Theory II: Quantum Electrodynamics A Bridge between Mathematicians and Physicists - Zeidler, Eberhard (Springer Berlin Heidelberg : Imprint: Springer, 2009)
This is the second volume of a modern introduction to quantum field theory which addresses both mathematicians and physicists ranging from advanced undergraduate students to professional scientists. This book seeks to bridge the existing gap between the different languages used by mathematicians and physicists. For students of mathematics it is shown that detailed knowledge of the physical background helps to discover interesting interrelationships between quite diverse mathematical topics. For students of physics fairly advanced mathematics, beyond that included in the usual curriculum in physics, is presented. The present volume concerns a detailed study of the mathematical and physical aspects of the quantum theory of light.